Survey of Income and Program Participation (SIPP) 1987 Full Panel Research File ([Verlag nicht ermittelbar], 1991)
This data collection contains basic demographic, social, and economic data for each member of interviewed households in the first seven waves of the 1987 Panel of SIPP. Variables include age, sex, race, ethnic origin, marital status, household relationship, education, and veteran status. Limited data are provided on housing unit characteristics such as number of units in structure and tenure. Core questions, repeated at each interview, cover monthly labor force activity, types and amounts of monthly income, and participation in various cash and noncash benefits programs for each month of the survey period. Data for employed persons include number of hours and weeks worked, earnings, and weeks without a job. Nonworkers are classified as unemployed or not in the labor force. In addition to income data associated with labor force activity, nearly 50 other types of income data are provided. Several variables are included for use in identifying longitudinal households and persons in them and to aid in analysis.